Pelestarian Nilai Perjuangan melalui Sinergi Legiun Veteran Republik Indonesia (LVRI) dan Pemuda Panca Marga (PPM) di Kabupaten Bojonegoro - Siswoyo Ambali; Adi Kurnia Saputra (Indo Publishing, 2025)
Veteran and youth organizations play a crucial role in preserving and safeguarding the values ​​of the nation's struggle.. This paper examines how this synergy operates, the types of activities implemented, and its impact on preserving local values ​​of struggle. The research employed a qualitative approach, collecting data through documentation, observations of PPM and LVRI activities, and interviews with administrators and members in Bojonegoro. The results indicate that the synergy between the Veterans Legion of the Republic of Indonesia (LVRI) and Pemuda Panca Marga (PPM) in Bojonegoro Regency has proven to be an effective collaborative model for preserving and safeguarding the values ​​of the nation's struggle. Joint activities such as state ceremonies, historical education, and social activities not only strengthen national identity but also strengthen emotional and historical bonds between generations.